2018
DOI: 10.1080/07391102.2018.1492970
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory molecular modelling, DNA interactions, antioxidant, antimicrobial, anticancer and biothermodynamic studies of bioactive water soluble mixed ligand complexes

Abstract: A novel series of bioactive water soluble mixed ligand complexes (1-5) [M(L)(phen)AcO]. nHO {where M = Cu (1) n = 2; Co (2), Mn (3), Ni (4), n = 4 and Zn (5) n = 2} were synthesized from 2-(2-Morpholinoethylimino) methyl)phenol Schiff base ligand (LH), 1, 10-phenanthroline and metal(II) acetate salt in a 1:1:1 stoichiometric ratio and characterized by several spectral techniques. The obtained analytical and spectral data suggest the octahedral geometry around the central metal ion. Density functional theory ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 71 publications
0
23
0
Order By: Relevance
“…Moreover, Ross and coworkers reported that the enthalpy changes (DH ) and entropy changes (DS ) occurred in the following order: (a) hydrophobic forces / DH > 0 and DS > 0, (b) van der Waals interaction and hydrogen bonding / DH < 0 and DS < 0, (c) electrostatic interactions / H < 0 or DH z 0 and DS > 0. 21,52 The observed results DH < 0 and DS < 0 clearly described that the interactions between complexes (1-5) and DNA could be attributed to van der Waals forces and hydrogen bonding. However, the loss of translational and rotational degrees of freedom and the interaction of counter ions along with hydrophobic forces in the complex-DNA adduct could provide for negative entropy and enthalpy changes with an exothermic effect.…”
Section: Evaluation Of the Biothermodynamic Parametersmentioning
confidence: 76%
See 3 more Smart Citations
“…Moreover, Ross and coworkers reported that the enthalpy changes (DH ) and entropy changes (DS ) occurred in the following order: (a) hydrophobic forces / DH > 0 and DS > 0, (b) van der Waals interaction and hydrogen bonding / DH < 0 and DS < 0, (c) electrostatic interactions / H < 0 or DH z 0 and DS > 0. 21,52 The observed results DH < 0 and DS < 0 clearly described that the interactions between complexes (1-5) and DNA could be attributed to van der Waals forces and hydrogen bonding. However, the loss of translational and rotational degrees of freedom and the interaction of counter ions along with hydrophobic forces in the complex-DNA adduct could provide for negative entropy and enthalpy changes with an exothermic effect.…”
Section: Evaluation Of the Biothermodynamic Parametersmentioning
confidence: 76%
“…More detail are given in our previous report. 21 Synthesis of the Schiff base ligand (HL) and its complexes (1)(2)(3)(4)(5) Details of the synthesized ligand (HL) and its complexes (1)(2)(3)(4)(5) together with information from the various structural characterization studies are enclosed in the ESI † (Scheme 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[8][9][10] Furthermore, the metal complexes of Schiff compounds have been of main attention for a lengthy time due to their capability to join oxygen to redox systems 11 that are oxidizing DNA. 12 They showed noteworthy antimicrobial activity owing to the free radical scavenging capability of their metal composites. Many research groups have been concerned in the chemical synthesis and biological testing of Schiff bases.…”
Section: Introductionmentioning
confidence: 99%